Positive-stimulus information is not “positive” for indirect transfer: Influence of successive informed-reversal training on oddity learning in Japanese monkeys - KOMAKI, JUNJI (Japanese Psychological Research, 1991)
Three groups of male Japanese monkeys were given two block discrimination training in WGTA. Two groups of subjects were trained in modified successive reversals. Before each reversal, one group (Group PSI, n=3) was presented with positive stimulus for the next reversal and the response to it was rewarded. Another group (Group NSI, n=4) was informed of negative stimulus by being exposed to unbaited new negative stimulus. The reversals were repeated for 30 and 20 times for the first and the second blocks of training, respectively. Still another group (Group OT, n=4) was given two blocks of overtraining trials. Before, in the middle of, and after the two blocks of training, the subjects of all three groups were faced with a series of oddity task probes. Group NSI manifested significantly better performance on the first trials of the oddity problems (ps<.01) than the other groups which were not different from each other. Oddity performance of three subjects in Group NSI was significantly different from chance level (ps<.05). NSI reversals proved to improve oddity learning. The implications of the results were discussed with reference to the hypothesis theory and the attention theory of learning-set formation.